SYSTEMATIC LITERATUR REVIEW: APAKAH KEMANDIRIAN BELAJAR MEMPENGARUHI KEMAMPUAN KOMUNIKASI MATEMATIS SISWA? - Adinda Cahyani; Meiliasari Meiliasari; Wardani Rahayu (LPPM Universitas Bina Bangsa, 2024)
The importance of mastering mathematical communication skills and independent learning in the 21st century. This research finds out whether learning independence affects mathematical communication skills. This research uses a literature study methodology or Systematic Literature Review (SLR). This research collects data by taking data from literary sources, reading, taking notes, and processing these sources as research material The research analyzed 35 articles that had been accredited in the literature review obtained from Google Scholar, Research Gate, Publish or Perish, Taylor & Francis, Science Direct, and DOAJ. The results of this research are that soft skills can influence hard skills, namely learning independence can influence mathematical communication skills which have an impact on improving student learning outcomes.